근위대퇴부 정면 영상을 이용한 골다공증 평가 시 방사선적 계측의 진단일치도 - 강영한(Yeong-Han Kang); 조광호(Kwang-Ho Cho) (한국콘텐츠학회 논문지, 12(6), 2012)
The purpose of this study was to determine whether there are relationships between radiologic parameters for osteoporosis by the proximal femur radiograhps and bone mineral density, as assessed by Dual Energy X-ray Absorptiometry(DEXA). Proximal femur anterior-posterior projection were taken from 112 individuals who undergoing DEXA. Radiographic parameters including canal-to-calcar ratio(CCR) and cortical thickness indices(CTI) were measured and compared with bone mineral density($g/cm^2$), T-score. The intramedullary femoral canal width(FW) and calcar width(CW) at osteoporosis group was significantly larger than that of control group. The CCR were correlated negatively with bone mineral density($g/cm^2$)(r=-0.340, p<0.01), and the CTI were correlated positively(r=0.624). The diagnostic accuracy of CCR for osteoporosis was 63.4%, and kappa value was 0.271. And the accuracy of CTI was 67.0%, and kappa value was the level of fair agreement(${κ}$=0.258). The proximal femur with large CCR and small CTI had lower T-scores. When evaluating proximal femur anterior-posterior radiographs, those patients with the thinnest femur diaphyseal cortices should be referred for further osteoporosis investigation. 본 연구는 근위대퇴골 정면 영상에서 골다공증 측정을 위한 영상지표가 이중에너지흡수계측법(DEXA)으로 측정한 골밀도 결과와 관련성이 있는지 알아보고자 하였다. 총 112명을 대상으로 근위대퇴부 정면 영상을 촬영하였고, 영상 지표인 대퇴골관비(CCR)와 피질골 두께지표(CTI)를 측정하여 DEXA 골밀도 결과와 비교하였다. T-score를 이용하여 골다공증군과 비골다공증군으로 나누었고, 영상지표와 평균비교분석 및 상관관계분석, 진단일치도를 비교하였다. 영상계측에서 골다공증군의 골수강내 대퇴관과 골단 대퇴관 간격은 비골다공증군보다 유의하게 컸다. CCR은 골밀도와 음의 상관관계(r=-0.340)가 이었고, CTI는 양의 상관관계(r=0.624)가 있었다. 골다공증에 대한 CCR의 진단일치도는 63.4%이었고, kappa 값은 0.271이었다. CTI의 진단일치도는 67.0%이었고, kappa 값은 0.258 이었다. 결론적으로 근위대퇴골 영상에서 비골다공증군보다 골다공증군의 CCR이 더 크고, CTI는 더 좁게 나타났다. 이는 근위대퇴골 정면영상을 평가할 때 대퇴골의 골단간 피질의 두께가 얇은 환자는 골다공증에 대한 추가적인 검사를 추천할 수 있다.